Analisis Cost Structure dengan Metode Variable Costing pada Rumah Sakit - Retnaning Tyas; Yanneri Elfa Kiswara Rahmantya (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
This study aims to provide a solution for hospitals in compiling a cost structure using the variable costing method. Proper cost management is crucial for hospitals. This is because hospitals have limitations in maximizing profits. So the only alternative to survive in this industry is cost optimization. In previous studies, many have emphasized financing with the activity based cost system method. In this study, it was found that there are many weaknesses if the hospital uses the activity based cost system method. This weakness actually makes the hospital bear greater costs. An alternative that can be used by hospitals to develop a hospital cost structure is to use variable costing. The variable costing method distinguishes costs into three parts, namely fixed costs, variable costs and semi-variable costs.